CAN SPEED, ATTACK ANGLE AND CUTTING FORCE, AFFECT THE QUALITY OF SUGARCANE HARVEST? - Moura, Michel Dos Santos [UNESP]; Filho, Aldir Carpes Marques [UNESP]; Grudtner, Guinther Hugo; Lanças, Kléber Pereira [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2021)
The base cut of cultures is one of the most studied parameters, and the variables involved in this process should be better evaluated under controlled conditions. The aim of this study was to evaluate, using an electromechanical device, under controlled conditions, the influence of the cutting angle and the machine's translation speed on the impact force generated on sugarcane stalks in mechanized harvesting. The study was carried out at the Nempa-Center for Testing of Agroforestry Machines and Tires (NEMPA) at UNESP/Botucatu. For the tests, the Sugarcane Basal Cut Testing Device (BCTD) was used. The collected data were evaluated using multiple linear regression analysis, using the stepwise method. The results showed that the angle of the cutting blades is the most significant variable in relation to the impact force of the sugarcane stalk cutting process, overcoming the effect of the machine's translation speed.
¿PUEDEN LA VELOCIDAD, EL ÁNGULO DE ATAQUE Y LA FUERZA DE CORTE AFECTAR LA CALIDAD DE LA COSECHA DE LA CAÑA DE AZÚCAR?
A VELOCIDADE, ÂNGULO DE ATAQUE E FORÇA DE CORTE PODEM AFETAR A QUALIDADE DA COLHEITA DE CANA DE AÇÚCAR?
Keywords: Losses; Machine tests; Mechanization; Stalk damage